Composition of Primary and Secondary Metabolite Compounds in Seeds and Pods of Asparagus Bean (Vigna unguiculata (L.) Walp.) from China - Irina Perchuk; Tatyana Shelenga; Maria Gurkina; Elena Miroshnichenko; Marina Burlyaeva (Molecules, 2020)
Asparagus bean immature pods and seeds are popular as food products for healthy and functional nutrition. Gas chromatography with mass spectrometry was used to compare metabolomic profiles of seeds and pods yielded by old Chinese landraces and the modern cultivars ‘Yunanskaya’ and ‘Sibirskiy razmer’. About 120 compounds were identified. The content of a majority among groups of compounds was higher in pods than in seeds. The amount of free amino acids in pods was 47 times higher, polyols and phytosterols 5 times higher, phenolics 4 times higher, and organic acids and saponins 3 times higher than in seeds. Differences were found in the relative content of compounds. Among phenolic compounds, the dominant one for seeds was protocatechuic acid, and for pods 4-hydroxycinnamic acid. Only polyols were identified in seeds, but pods additionally contained ethanolamine, phytol, and phytosphingosine. The ratio for nonsaturated/saturated fatty acids was 2.2 in seeds and 1.4 in pods. Seeds contained more stigmasterol, and pods more β-sitosterol. Aglycones of saponins were identified: cycloartenol in seeds, α- and β-amyrins in pods. Oligosaccharides dominated in both seeds and pods. Landraces manifested higher protein content in pods, while modern cultivars had pods with higher contents of organic acids, polyols, monosaccharides, and fatty acids. The results obtained confirm the high nutritional value of asparagus bean seeds and pods, and the prospects of their use in various diets.